PEMBERIAN TERAPI BENSON DAN SLOW DEEP BREATHING UNTUK MENURUNKAN INTENSITAS NYERI PADA PASIEN POSTPARTUM DI RUANG DAHLIA RST BHAKTI WIRA TAMTAMA SEMARANG - Krisnawati, Amelia Devin; Wulaningsih, Indah (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Background: Postpartum or the postpartum period is the period after the placenta is born and ends when the uterine organs return to their pre-pregnancy state. The postpartum period or puerpurium starts from 1 hour after the birth of the placenta to 6 weeksab (42 days) after that. There are 3 stages of the postpartum period, namely: early puerperium, intermedial puerperium and remote puerperium.One distraction technique for pain relief is benson and slow deep breathing therapy. Classical music therapy can provide calm with soft strains that are in harmony with the pulse, therepy causing a distraction effect on thoughts about pain Objective: To describe the application of is benson and slow deep breathing therapy to treat pain in postpartum patients in the Dahlia Room RST Bhakti Wira Tamtama Semarang. Method: Using a descriptive method by describing nursing care for postpartum patients in the Dahlia Room RST Bhakti Wira Tamtama Semarang, using pre-test and post-test. The research was conducted on 05-07 December 2023. Results: After carrying out the benson and slow deep breathing therapy intervention to treat pain, the result showed a reduction in pain in postpartum patients. Conclusion: Clients are able to overcome pain by providing benson and slow deep breathing therapy. Pain is reduced from severe to mild, optimized with pharmacological pain management using analgesics as indicated. Suggestion: It is hoped that patients and families can carry out routine treatment and therapy programs.